SOEHARTO MUSEUM AS AN EDUCATIONAL MEDIUM: A QUALITATIVE STUDY ON THE EFFECTIVENESS AND CHALLENGES IN HISTORY EDUCATION - Susanna Stella Wulandari; Muhammad Iqbal Birsyada; Esti Setiawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is motivated by students’ low interest in history lessons, which is often caused by monotonous teaching methods. The research questions include: (1) How is the experience of learning history at the Soeharto Museum? (2) What materials and media are presented? and (3) What are the effectiveness and challenges of history learning in this museum? The objectives of this study are: (1) to describe the history learning experience at the Soeharto Museum, (2) to identify the materials and media used, and (3) to analyze the effectiveness and challenges encountered. This qualitative research was conducted through interviews with museum managers and visitors, non-participant observation, and documentation. The findings show that: (1) the Soeharto Museum is effective as a medium for historical education that is both empirical and affective, through collections, visual narratives, documentary films, and guided tours; (2) the materials and media, including interactive storytelling, discussions of values, national songs, and reflection activities, are tailored to visitors’ age levels, thus engaging cognitive, affective, and psychomotor domains; (3) the museum’s effectiveness is evidenced by positive responses from visitors and educational institutions, and by the adoption of similar methods by other museums. This experience- and emotion-based approach aligns with constructivist theory, although the main challenge remains maintaining relevance in the digital era. The museum addresses this through technological innovation and communicative educators.This research highlights the importance of collaboration between schools and museums to make history learning more contextual, reflective, and adaptive. The Soeharto Museum serves as an effective educational medium by integrating traditional and digital approaches to foster nationalism and historical awareness among younger generations.